Barnacles as biological flow indicators - Joseph W.N.L. Reustle; Benjamin A. Belgrad; Amberle McKee; Delbert L. Smee (PeerJ, 2023)
Hydrodynamic stress shapes the flora and fauna that exist in wave-swept environments, alters species interactions, and can become the primary community structuring agent. Yet, hydrodynamics can be difficult to quantify because instrumentation is expensive, some methods are unreliable, and accurately measuring spatial and temporal differences can be difficult. Here, we explored the utility of barnacles as potential biological flow-indicators. Barnacles, nearly ubiquitous within estuarine environments, have demonstrated notable phenotypic plasticity in the dimensions of their feeding appendages (cirri) and genitalia in response to flow. In high flow, barnacles have shorter, stockier cirri with shorter setae; in low flow, barnacles have longer, thinner cirri with longer setae. By measuring the relative differences in cirral dimensions, comparative differences in flow among locations can be quantified. We tested our hypothesis that ivory barnacles (Amphibalanus eburneus) could be useful biological flow indicators in two experiments. First, we performed reciprocal transplants of A. eburneus between wave protected and wave exposed areas to assess changes in morphology over 4 weeks as well as if changes dissipated when barnacles were relocated to a different wave habitat. Then, in a second study, we transplanted barnacles into low (<5 cm/s) and high flow (>25 cm/s) environments that were largely free of waves and shielded half of the transplanted barnacles to lessen flow speed. In both experiments, barnacles had significant differences in cirral morphologies across high and low flow sites. Transplanting barnacles revealed phenotypic changes occur within two weeks and can be reversed. Further, ameliorating flow within sites did not affect barnacle morphologies in low flow but had pronounced effects in high flow environments, suggesting that flow velocity was the primary driver of barnacle morphology in our experiment. These results highlight the utility of barnacles as cheap, accessible, and biologically relevant indicators of flow that can be useful for relative comparisons of flow differences among sites.